Immune responses and clinical outcomes following the third dose of SARS-CoV-2 mRNA-BNT162b2 vaccine in advanced breast cancer patients receiving targeted therapies: a prospective study - Nelli, Fabrizio; Fabbri, Agnese; Botticelli, Andrea; Giannarelli, Diana; Marrucci, Eleonora; Fiore, Cristina; Virtuoso, Antonella; Berrios, Julio Rodrigo Giron; Scagnoli, Simone; Pisegna, Simona; Cirillo, Alessio; Panichi, Valentina; et al. (Frontiers in Oncology, 2023)
Purpose: Metastatic breast cancer patients are the most prevalent oncology population with advanced disease facing COVID-19 pandemic. Immune responses after mRNA-based vaccination during treatment with CDK4/6 inhibitors or HER2-directed agents remain unclear. We conducted a prospective analysis to elucidate changes in antibody titers and lymphocyte counts following full course of mRNA-BNT162b2 (tozinameran) vaccination in recipients undergoing these targeted therapies. Methods: Patients who had received a booster dosing and had been treated for at least 6 months were eligible. Antibody titers against SARS-CoV-2 spike protein were measured at four subsequent time points. Immunophenotyping of circulating lymphocytes was performed before the third dose of tozinameran and four weeks later to quantify the absolute counts of CD3+CD4+ T-helper cells, CD3+CD8+ T-cytotoxic cells, CD19+ B cells, and CD56+CD16+ NK cells. We also assessed the incidence of breakthrough infections and investigated whether immune changes affect time-to-treatment failure (TTF) after booster vaccination. Results: The current analysis included 69 patients, of whom 38 (55%) and 31 (45%) were being treated with CDK4/6 inhibitors and HER2-targeted therapies, respectively. All participants received a third dose of tozinameran between September 23 and October 7, 2021. Multivariate analysis revealed that CDK4/6 inhibition predicted a significantly impaired humoral response after the booster dose. This detrimental effect was also evident for T-helper cell counts before the third immunization, but it disappeared in the subsequent evaluation. After a median follow-up of 22.3 months, we observed 19 (26%) cases of COVID-19 outbreaks, all experiencing favorable clinical outcomes. Univariate analysis showed a significant association between the onset of SARS-CoV-2 infections and the use of CDK4/6 inhibitors, as well as with an impaired antibody and T-helper cell response. Only the last two covariates remained independent predictors after multivariate testing. Dynamic variations in antibody titers and T-helper cell counts did not affect TTF in multivariate regression analysis. Conclusions: Our results confirm that the immune response to tozinameran is impaired by CDK4/6 inhibitors, increasing the odds of breakthrough infections despite the third vaccine dose. Current evidence recommends maintaining efforts to provide booster immunizations to the most vulnerable cancer patients, including those with advanced breast cancer undergoing CDK4/6 inhibition.